Entomological studies on the impact of a small-scale irrigation scheme on malaria transmission around Ziway, central Ethiopia - Kibret, S.; Boelee, Eline; Petros, B.; Tekie, H. (2010)
Larval and adult anophelines were sampled around Ziway, Central Ethiopia. Throughout the study period, significantly higher densities of Anopheles pharoensis and An. arabiensis were found in the village with irrigation than in the village without. Canal leakage pools, irrigated fields and irrigation canals were the major sources of Anopheles larvae. Most adult anophelines were found to feed on humans, especially before 22hrs, and up to 1% were infected with malaria parasites. This study demonstrated that due to poor maintenance, irrigation schemes create conducive breeding grounds for malaria vector mosquitoes and hence increase the risk of malaria transmission.